Novell ZENworks 7 Linux Management : Administrator's Handbook - Tanner, Ron; Whitehead, Richard (Sams, 2005)
Novell ZENworks Linux Management Administrator's Handbook is the official guide to ZENworks Linux Management, written by Ron Tanner, Novell ZENworks product manager, and Richard Whitehead, Novell ZENworks product marketing manager. Learn about the innovative combination of SUSE Linux and the advanced management capabilities of ZENworks that has positioned Novell as the leading enterprise Linux solution provider. You will learn about: The ZENworks family The ZENworks Management web console Registering devices into them system and system settings Reporting Common device management tasks Keeping servers synchronized Troubleshooting Gather insight directly from the minds behind ZENworks Linux Management with the Novell ZENworks Linux Management Administrator's Handbook.